2020
DOI: 10.7759/cureus.9277
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acne Vulgaris and Its Association With Lifestyle Among Adolescents and Young Adults in Hail, Kingdom of Saudi Arabia: A Community-Based Study

Abstract: Acne vulgaris is the commonest dermatological problem internationally and nationally. Its incidence is increasing every year in the Kingdom of Saudi Arabia (KSA). Though it is not a major health issue but it significantly affects the patient cosmetically, psychologically and socially. Previous studies have shown its association with lifestyle (age, diet, stress, sleep, smoking, exercise, obesity, etc.) and family history. By simple cost-effective lifestyle modification, its occurrence and late consequences cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…We categorized skin types of AV patients into five groups including oily (417, 37.27%), combination (497, 44.41%), neutral (115, 10.28%), dry (45, 4.02%), and sensitive (42, 4.02%). Previous studies have shown a highly significant association between skin types and AV; [ 3 ] we also found that there was a significant association between skin type and grade of severity in AV patients ( P = 0.04; Supplementary Table 2). There were 59.16% (662) patients who thought skin care products could improve AV, and 71.85% (804) patients who thought dermocosmetics could improve the clinical manifestation of AV.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…We categorized skin types of AV patients into five groups including oily (417, 37.27%), combination (497, 44.41%), neutral (115, 10.28%), dry (45, 4.02%), and sensitive (42, 4.02%). Previous studies have shown a highly significant association between skin types and AV; [ 3 ] we also found that there was a significant association between skin type and grade of severity in AV patients ( P = 0.04; Supplementary Table 2). There were 59.16% (662) patients who thought skin care products could improve AV, and 71.85% (804) patients who thought dermocosmetics could improve the clinical manifestation of AV.…”
supporting
confidence: 78%
“…The prevalence of AV among adolescents ranges from approximately 40% to 90%, increasingly affecting adults as well, whereas women are more frequently affected than men. [ 3 ] Of the 1119 participants, there were 798 females (71.31%) and 321 (28.69%) males. The participant age range was 11 to 69 years; the age was 28.32 ± 7.96 years, and the characteristics of AV patients in different age groups are shown in Supplementary Table 1.…”
mentioning
confidence: 99%
“…There are limited number of studies investigating the relationship between acne and physical activity. Alshammrie et al did not find a significant relationship between physical exercise and acne (29). Similarly, in another study conducted in Tehran, it was reported that there was no relationship between physical activity and acne (30).…”
Section: Discussionmentioning
confidence: 91%
“… 39 In addition, two studies conducted in Jeddah among final year and first-year medical students found that the prevalence of acne vulgaris was high in females with a prevalence of 98% and 58.8%, respectively. 40 , 41 In Alexandria, an Egyptian study showed a higher prevalence among females, confirmed clinically, and their age ranged from 15 to 18 years with a mean age of 16.31 ± 0.725. 42 There are many reasons, connected to hormonal imbalances, that can affect female acne development, such as polycystic ovary syndrome where acne is one of the main symptoms.…”
Section: Discussionmentioning
confidence: 95%